Estratégia metacognitivas na resolução de problemas em física - Ghiggi, Caroline Maria (2017)
Metacognition has received special attention in studies involving learning and, gradually, it has been taking up space in the educational context, especially by promoting the autonomy and enhance learning. Based on this identification and on the study of Rosa (2011), who showed the pertinence of its association with experimental activities in Physics, the present study is concerned with develop ment and analising didactic proposals that allow the approximation of this construct with problem solving in Physic s. Inserted in the research line theoretical-methodological foundations for the teaching of Sciences and Mathematics, this study elects a teacher training course in Physics as research focus And infers the following question as guiding the research: How do future Physics teachers conceive structured problem solving based on a metacognitive orientation? The object of the study is to identify the possibilities of associating the metacognitive strategies with the solving of problems in Physics, Evaluating their didactic pertinence in the voice of future teachers. To respond to this questioning and achieve the intended objective, the study structures four didactic proposals for problem solving oriented by metacognition structured in different ways. These proposa ls were so-called: guiding prompts; Rrewriting the statement and outlining the problem situation; explanation of the pro blem situation to a colleague and problem solving with elaboration of predictions. Each proposal is accompanied by the discussions that support its elaboration and operationalization in the form of metacognitive strategies. The evaluation of the proposal in the form of study research was performed through an intervention process with a group of undergraduate Physics students from Universit y of Passo Fundo. The intervention in the modality course of university extension was evaluated through three instruments: logbook filled by the researcher , materials produced by participants and semistructured interviews with students who participated in all meetings. The analysis of the data collected allowed pointing the viability of the four structured educational proposals and it showed that future teachers have a concern about creating opportunities for the qualification of learning of their future students and, for this, they show themselves opened to discuss and analyze didactic alternatives. In addition, it has shown that the proposals can represent benefits to learning, especially in terms of contributing so that the students are more reflexive and autonomous in their learning. Finally, the study points to the importance of offering materials that are available to teachers as an approximation of academic research to the classroom and infers the importance of making these materials available to teachers and future physics teachers. In this sense, the study draws up a support material for teachers, which constitute the educational product of this dissertation, making it available in digital and printed form.